Effects of Individual Changes in Training Distribution on Maximal Aerobic Capacity in Well-Trained Cross-Country Skiers: A Follow-Up Study - Johansen, Jan-Michael; Sunde, Arnstein; Helgerud, Jan; Gjerløw, Lars Erik; Støren, Øyvind (Frontiers in Physiology, 2021)
The purpose of this study was to evaluate changes in training characteristics following a year with no substantial changes in training, and the subsequent effects on maximal oxygen uptake (VO2max) among already well-trained cross-country skiers. Six cross-country skiers, which were participants in a larger previous study, volunteered for a follow-up study. All skiers performed self-motivated changes in training characteristics for a new preparation period in this follow-up, generally by more high-intensity training (HIT). All training characteristics were registered from training diaries. During the follow-up period, all skiers performed an incremental VO2max test in February 2020 and August 2020. Training were categorized into three different training periods; 1) February 2019 to February 2020 (P1) representing the training performed prior to the follow-up, 2) February 2020 to July 2020 (P2) and 3) July 2020 to August 2020 (P3). On average, the skiers increased their VO2max by 5.8±5.0% (range: -1.8 - +10.2%) during the follow-up study compared to the average VO2max during the preceding year. Total training volume increased on average by 10.0% and 25.7% in P2 and P3 respectively, compared to P1. The average volume of HIT was similar between P1 and P2, but increased 62.8% in P3. However, large individual differences in training changes were observed. In conclusion, the present study revealed that considerable changes in training characteristics generated an increased VO2max in several already well-trained cross-country skiers. Reduced total training volume and increased or maintained HIT volume seemed to be a beneficial change.